(untitled) (Law, State and Telecommunications Review, 2026)
[Purpose] This article examines the rapid expansion of AI-driven data centers in Latin America, underscoring the friction between digital development goals and environmental sustainability imperatives. This study highlights the paradox of a region that, despite possessing a predominantly renewable energy matrix, confronts structural infrastructure constraints. These limitations are driving a new form of extractivism, posing threats to water security, grid stability, and regional sovereignty. [Methodology/approach/design] Adopting a qualitative, interdisciplinary methodology, the study integrates legal and regulatory frameworks, strong sustainability theory, and engineering-based quantitative metrics. Three methodological pillars ground this analysis: a systematic review of academic and technical literature; an in-depth examination of market reports, international agency documents, and government procedures; and comparative case studies focused on governance conflicts in Latin American countries, with emphasis on the Brazilian legislative context. To support the analysis of these findings, the article is organized into four analytical sections, namely: (i) The Hidden Face of AI: Critical Analysis of Social-Environmental and Structural Impacts; (ii) Fragmented Governance and Regional Risk: LATAM Cases; (iii) Regulatory Arbitrage of data centers Between the Global North and South: Governance, Sovereignty and Alternative Responses and Resistances; and (iv) Overcoming the Extractivist Paradigm: Proposal for an Integrated Regulatory Framework Based on the Concept of Systemic Governance. [Findings] The findings underscore that the projected exponential growth in energy demand from data centers will strain constrained transmission grids and deepen fossil fuel dependence, thereby challenging the prevailing ’green data center’ narrative. The benefits, such as job creation, tend to be short-lived, while tax incentives erode public revenues. The study also reveals hidden environmental costs embedded in hardware lifecycles, contributing to transboundary e-waste flows and toxic “waste colonialism.” Case studies demonstrate patterns of governance failure, regulatory arbitrage, and socio-environmental conflict, particularly affecting local and Indigenous communities. [Practical implications] This study argues for a proactive governmental role and proposes an integrated regulatory framework grounded in systemic governance. [Originality/value] By presenting a comprehensive diagnosis and a technically grounded governance framework, this study contributes an original roadmap seeking to guide policymakers, investors, and civil society toward a truly just and sustainable digital transition.